A histone deacetylase 7-derived peptide promotes vascular regeneration via facilitating 14-3-3γ phosphorylation. (29th January 2020) - Yang, Junyao; Moraga, Ana; Xu, Jing; Zhao, Yue; Luo, Peiyi; Lao, Ka Hou; Margariti, Andriana; Zhao, Qiang; Ding, Wei; Wang, Gang; Zhang, Min; Zheng, Lei; et al.
Abstract: Histone deacetylase 7 (HDAC7) plays a pivotal role in the maintenance of the endothelium integrity. In this study, we demonstrated that the intron-containing Hdac7 mRNA existed in the cytosol and that ribosomes bound to a short open reading frame (sORF) within the 5′-terminal noncoding area of this Hdac7 mRNA in response to vascular endothelial growth factor (VEGF) stimulation in the isolated stem cell antigen-1 positive (Sca1 + ) vascular progenitor cells (VPCs). A 7-amino acid (7A) peptide has been demonstrated to be translated from the sORF in Sca1 + -VPCs in vitro and in vivo. The 7A peptide was shown to receive phosphate group from the activated mitogen-activated protein kinase MEKK1 and transfer it to 14-3-3 gamma protein, forming an MEKK1-7A-14-3-3γ signal pathway downstream VEGF. The exogenous synthetic 7A peptide could increase Sca1 + -VPCs cell migration, re-endothelialization in the femoral artery injury, and angiogenesis in hind limb ischemia. A Hd7-7sFLAG transgenic mice line was generated as the loss-of-function model, in which the 7A peptide was replaced by a FLAG-tagged scrabbled peptide. Loss of the endogenous 7A impaired Sca1 + -VPCs cell migration, re-endothelialization of the injured femoral artery, and angiogenesis in ischemic tissues, which could be partially rescued by the addition of the exogenous 7A/7Ap peptide. This study provides evidence that sORFs can be alternatively translated and the derived peptides may play an important role in physiological processes including vascular remodeling. : Abstract : VEGF induced the translation of a 7-amino acid peptide (7A) from Hdac7 mRNA in mouse adventitial Sca1+ vascular progenitor cells, which formed a novel MEKK1-7A-14-3-3γ signal pathway downstream VEGF and contributed to vascular injury repair and neo-angiogenesis in ischemic tissues. The deficiency of 7A peptide (7A-null mice) retarded these processes, which could be rescued by exogenous 7A peptide.